BRASIL Y URUGUAY: LA HISTORIA REGIONAL EN EL DISCURSO MILITAR URUGUAYO (1973-1985) (Revista de História Regional, 2007)
This article analyzes the place given to Brazil inUruguayan history, written by Uruguays military, in adidactic book published in 1980. Members of the military inan attempt to justify the political violence the country hadbeen put through, ventured to write history. This history isvery nationalistic and consequently made them praise theconflicts throughout Uruguayan history, with Brazil. Sinceboth dictatorships shared the same philosophy, this speechcould not only stress the differences between the countriesand therefore went back and forth between friend and enemyalmost simultaneously. The main topics of the study are:language, Uruguays independence, the problem of boundariesand soccer. These are the points that both countries aremore in contact with and at the same time have moredifferences.